TERAPIA FOTODINAMICĂ ÎN CONTROLUL BIOFILMULUI MICROBIAN ORAL. DATE DIN LITERATURA - Mârţu- Stefanache; Solomon Sorina Mihaela; Mârţu Silvia (Romanian Dental Association for Education, 2016)
Microbial biofilms in the oral cavity are involved in the etiology of various oral conditions, including periodontal and dental implant failures. It is therefore not surprising that bacteria growing in dental plaque, a naturally occurring biofilm, display increased resistance to antimicrobial agents . Current treatment techniques involve either periodic mechanical disruption of oral microbial biofilms or maintaining therapeutic concentrations of antimicrobials in the oral cavity, both of which are fraught with limitations. The development of alternative antibacterial therapeutic strategies therefore becomes important in the evolution of methods to control microbial growth in the oral cavity. In this review, we propose to provide an overview of photodynamic therapy with emphasis on its current status as an antimicrobial therapy to control oral bacteria, and review the progress that has been made, concerning the applications of photodynamic therapy for targeting biofilm-associated oral infections and new frontiers of antimicrobial photodynamic therapy research will be introduced, including targeting strategies and thereby providing the opportunity for more effective disease prevention and control.